Outcome of allogeneic transplantation for mature T-cell lymphomas: impact of donor source and disease characteristics - Hamadani, Mehdi; Ngoya, Maud; Sureda, Anna; Bashir, Qaiser; Litovich, Carlos Alejandro; Finel, Hervé; Chen, Yue; Boumendil, Ariane; Zain, Jasmine; Castagna, Luca; Cashen, Amanda F.; Blaise, Didier; et al. (Blood advances, 2022)
Mature T-cell lymphomas constitute the most common indication for allogeneic hematopoietic cell transplantation (allo-HCT) of all lymphomas. Large studies evaluating contemporary outcomes of allo-HCT in mature T-cell lymphomas relative to commonly used donor sources are not available. Included in this registry study were adult patients who had undergone allo-HCT for anaplastic large cell lymphoma, angioimmunoblastic T-cell lymphoma (AITL), or peripheral T-cell lymphoma not otherwise specified (PTCL-NOS) between 2008 and 2018. Hematopoietic cell transplantation (HCT) platforms compared were posttransplant cyclophosphamide-based haploidentical (haplo-)HCT, matched sibling donor (MSD) HCT, matched unrelated donor HCT with in vivo T-cell depletion (MUD TCD+), and matched unrelated donor HCT without in vivo T-cell depletion (MUD TCD−). Coprimary end points were overall survival (OS) and progression-free survival (PFS); secondary end points included nonrelapse mortality (NRM), and relapse/progression incidence (RI). A total of 1942 patients were eligible (237 haplo-HCT; 911 MSD; 468 MUD TCD+; 326 MUD TCD−). Cohorts were comparable for baseline characteristics with the exception of higher proportions of patients with decreased performance status (PS) and marrow graft recipients in the haplo-HCT group. Using univariate and multivariate comparisons, OS, PFS, RI, and NRM were not significantly different among the haplo-HCT, MSD, MUD TCD+, and MUD TCD− cohorts, with 3-year OS and PFS of 60%, 63%, 59%, and 64%, respectively, and 50%, 50%, 48%, and 52%, respectively. Significant predictors of inferior OS and PFS on multivariate analysis were active disease status at HCT and decreased PS. AITL was associated with significantly reduced relapse risk and better PFS compared with PTCL-NOS. Allo-HCT can provide durable PFS in patients with mature T-cell lymphoma (TCL). Outcomes of haplo-HCT were comparable to those of matched donor allo-HCT.
Gesehen am 25.03.2022